Descolonizando el conocimiento - Dupuits, Emilie (2024)
In Ecuador, the Andean highlands ecosystems, also known as páramos, are essential for producing water for human consumption and irrigation. Some páramos in the country are managed by indigenous communities that have contributed to their conservation through principles of reciprocity, territory and culture. However, these community-led initiatives are often marginalized by techno-scientific discourses and visions of water as promoted by public authorities as well as international experts working on these issues. Faced with these limitations, local water justice movements advocate for a more politicized approach that aims to shed light on the unequal distribution of benefits, access and control over water, as well as the tensions surrounding water rights, knowledge and cultural practices. This article draws on a case study in the communities of Cangahua, located in the northern highlands of Ecuador, where the Ñukanchik Urku páramo committee is contributing to watershed conservation based on community management principles. This study aims to examine the processes of decolonizing knowledge around water conservation practices in the community páramo of Ñukanchik Urku. Using participatory and transdisciplinary research methods from a decolonial perspective, this article questions the boundaries between techno-scientific and local and indigenous knowledge regarding water conservation.